두유, 이눌린, 쌀가루를 첨가한 푸딩의 품질 특성 및 위장관 시뮬레이션에서 프로바이오틱스의 생존력에 미치는 영향 - 윤승화(Seungwha Yoon); 임승용(Seung-Yong Lim) (한국식품과학회지, 2023)
This study aimed to investigate the viability of probiotics in the gastrointestinal simulation and quality characteristics of pudding containing soymilk, inulin, and/or rice. The puddings were produced by mixing a pudding base and yogurt with probiotics. The quality properties and acid/bile tolerance of the puddings were determined over a period of 4 weeks during cold storage. Three pudding formulations were evaluated by panelists: MC (milk control), MIR (milk, inulin, rice), and MSIR (milk, soymilk, inulin, rice). MIR, MSI (milk, soymilk, inulin), and MSIR showed a lower pH and higher acidity than MC. There was no significant difference in the viability of probiotics between samples. In the acid/bile resistance, MSIR showed a significantly higher viability than MC. However, it showed a stronger beany flavor and sourness while the sweetness was weaker compared to MIR. In the preference, MSIR had a significantly lower value than MIR. Therefore, MIR has potentials as a synbiotic pudding, considering consumer preferences and the protective effect of probiotics. KCI Citation Count: 0